PROSPECTS OF APPLICATION OF TISSUE-ENGINEERED PANCREATIC CONSTRUCTS IN THE TREATMENT OF TYPE 1 DIABETES - G. N. Skaletskaya; N. N. Skaletskiy; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2017)
Allotransplantation of pancreatic islets remains the most effective method of treatment of diabetes mellitus type 1 being capable under combination of favorable conditions (suffi cient number of isolated islets, effective combination of immunosuppressive drugs) to reach the recipients’ insulin independence for several years. However, the overwhelming shortage of donor pancreas and limited post-transplantation islet survival do not allow increasing the number of such transplants and their effectiveness. This review presents a critical analysis of the work done by Russian and foreign authors onto creation of tissue-engineered pancreatic constructs that may lead to the resolution of the three main pancreatic islet transplantation issues: 1) lack of donor material; 2) necessity of immunosuppressive therapy; 3) limited survival and functional activity of the islet.